2019
DOI: 10.1039/c9nr00103d
|View full text |Cite
|
Sign up to set email alerts
|

Rapid formation of small mixed-valence luminescent silver clusters via cation-coupled electron-transfer in a redox-active porous ionic crystal based on dodecamolybdophosphate

Abstract: Rapid formation of small mixed-valence luminescent silver clusters via cation-coupled electron-transfer by redox-active polyoxometalate-based porous crystals is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…71 The PIC containing Ag 4 2+ in the micropores showed high sorption capacities for unsaturated hydrocarbons (acetylene and ethylene). 70 These results indicate that redoxactive PICs can serve as a platform to synthesize mixed-valence metal nanoclusters as catalysts.…”
Section: +mentioning
confidence: 89%
See 1 more Smart Citation
“…71 The PIC containing Ag 4 2+ in the micropores showed high sorption capacities for unsaturated hydrocarbons (acetylene and ethylene). 70 These results indicate that redoxactive PICs can serve as a platform to synthesize mixed-valence metal nanoclusters as catalysts.…”
Section: +mentioning
confidence: 89%
“…69 We have recently reported the formation of a mixed-valence luminescent silver cluster Ag 4 2+ using a redox-active PIC of (Figure 9). 70 The formation of Ag 4 2+ took less than 1 min, while the simple ion-exchange between Cs + and Ag + from aqueous AgNO 3 solution took more than 24 h. A model fitting of the time course of PL intensity has shown that the reduction-induced ion-exchange consists of two steps: electron transfer from the reduced POM ([α-PMo VI 11 -Mo V O 40 ] 4¹ ) to Ag + and subsequent formation of a silver cluster (Ag 4…”
Section: Redox-active Picsmentioning
confidence: 99%
“…(ii) POM-based ionic solids as cation-exchangers: the next target would be to explore cooperative effects of the selectively adsorbed cations and POMs,55 especially as optical materials, magnetic materials, solid catalysts, etc. (iii) Reduction-induced cation-uptake in POM-based ionic solids: while it is difficult for conventional porous compounds such as zeolites and MOFs to support the geometry change in the framework that often accompany the redox processes, POM-based solids show great potential for the multiple and reversible uptake/release of cations with electrons 6064,73. Such CCET reactions in solids can be applied not only to selective cation-uptake and sensing but also to the next-generation rechargeable batteries,76 solid catalysts for water splitting, chemical fixation of CO 2 , ammonia synthesis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…), and subsequent formation of a mixed-valence luminescent silver cluster Ag 4 2+ took <1 min (eqn (5)), while the simple ion-exchange with Cs + in Cs-ox with Ag + from AgNO 3 (aq.) took >24 h (eqn (6)):73Cs 2 [Cr 3 O(OOCH) 6 (4-methylpyridine) 3 ] 2 [α-PMoVI11Mo V O 40 ] + 2Ag + → Ag I Ag 0 [Cr 3 O(OOCH) 6 (4-methylpyridine) 3 ] 2 [α-PMoVI12O 40 ] + 2Cs + , Cs[Cr 3 O(OOCH) 6 (4-methylpyridine) 3 ] 2 [α-PMoVI12O 40 ] + Ag + → Ag I [Cr 3 O(OOCH) 6 (4-methylpyridine) 3 ] 2 [α-PMoVI12O 40 ] + Cs + .…”
Section: Reduction-induced Cation-uptake In Polyoxometalate-based Ionmentioning
confidence: 99%
“…Specifically, small mixed-valence Ag cluster (mainly [Ag 4 ] 2 + ) without any protecting ligands were formed and stabilized in a redox-active porous ionic crystal (PIC) based on [α-PMo 12 O 40 ] 3À . [14] The Ag cluster is formed via a cation-coupled electron transfer (CCET) reaction, [15] in which electrons are transferred from the reduced POM to Ag + and subsequent aggregation occurs according to the following reaction: ) with closed pores, [16] instead of Keggin-type POM with continuous pores, [14] is utilized as a scaffold to synthesize mixed-valence Ag clusters.…”
mentioning
confidence: 99%